Dual-delivery of FGF-2/CTGF from Silk Fibroin/PLCL-PEO Coaxial Fibers Enhances MSC Proliferation and Fibrogenesis - Ruodan Xu (Scientific Reports, 2017)
Abstract The success of mesenchymal stem cell transplantation is highly dependent on their survival and controlled fate regulation. This study demonstrates that dual-delivery of connective tissue growth factor (CTGF) and fibroblast growth factor 2 (FGF-2) from a core-shell fiber of Silk Fibroin/poly(L-lactic acid-co-ε-caprolactone)-polyethylene oxide (SF/PLCL-PEO) enhanced fibrogenic lineage differentiation of MSCs. The core-shell structure was confirmed by transmission electron microscopy (TEM), fluorescence microscopy and attenuated total reflection (ATR) Fourier transform infrared (FTIR) spectroscopy. A sequential release of FGF-2 and CTGF was successfully achieved in this manner. FGF-2 plays an important role in stem cell proliferation and, meanwhile when accompanied with CTGF, has a slightly additive effect on fibrogenic differentiation of MSCs, whereas CTGF promotes fibrogenesis and alleviates osteogenesis, chondrogenesis and adipogenesis.